OPPORTUNITIES AND CHALLENGES OF ENGLISH EDUCATION INDUSTRY IN POST COVID-19 PANDEMIC - Nurchalis, Nur Fadillah; R, Muh. Faizal; Noni, Nurdin (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
The language education industry sector has undergone significant transformations due to the Covid-19 pandemic, prompting a need for businesses to adapt to uncertain circumstances. This research aims to explore the opportunities and challenges encountered by entities in the English language education sector after these dynamic times. Employing a qualitative descriptive design, the study focuses on managers of English language courses and training institutions in the South Sulawesi region who volunteered as informants. The selection process utilized a snowball sampling technique, allowing for the inclusion of additional informants when necessary. Data collection involved interviews conducted through both zoom and in-person meetings. Analysis of the gathered data employed techniques from Miles and Huberman. The study's findings reveal interconnected opportunities and challenges faced by post-pandemic course managers, particularly concerning the implementation of distance learning. Consequently, strategies of affirmation are crucial to ensure the continued viability of businesses in the English language education industry.